2018
DOI: 10.1002/jum.14541
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Hemophilic Arthropathy: Sensitivity of Soft Tissue Discrimination With Musculoskeletal Ultrasound

Abstract: Introduction Point-of-care (POC) musculoskeletal ultrasound (MSKUS) is increasingly used by hemophilia providers to guide management, however, pathologic tissue differentiation with US is uncertain. We sought to determine the extent to which POC MSKUS can identify and discriminate pathologic soft tissue changes in hemophilic arthropathy. Materials and Methods 36 adult patients with hemophilia A/B were prospectively enrolled. POC MSKUS was performed on arthropathic joints (16 knees, 10 ankles, and 10 elbows) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…The results on the diagnostic accuracy of POC‐US for synovial hypertrophy are therefore expected to be valid for patient with moderate arthropathy too. This is supported by a very recent publication by von Drygalski et al showing that ultrasound is highly sensitive in the identification of abnormal soft tissue in patients with more advanced arthropathy (mean Pettersson score at joint level 8, range 0‐12) . More detailed ultrasound examination by an experienced musculoskeletal radiologist and/or using advanced ultrasound equipment is expected to reveal more subtle changes and may result in an even better diagnostic accuracy of ultrasound.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results on the diagnostic accuracy of POC‐US for synovial hypertrophy are therefore expected to be valid for patient with moderate arthropathy too. This is supported by a very recent publication by von Drygalski et al showing that ultrasound is highly sensitive in the identification of abnormal soft tissue in patients with more advanced arthropathy (mean Pettersson score at joint level 8, range 0‐12) . More detailed ultrasound examination by an experienced musculoskeletal radiologist and/or using advanced ultrasound equipment is expected to reveal more subtle changes and may result in an even better diagnostic accuracy of ultrasound.…”
Section: Discussionmentioning
confidence: 73%
“…Although soft tissue abnormalities in joints may be accurately evaluated by ultrasound, ultrasound differentiation between synovial hypertrophy with or without haemosiderin deposits is unreliable . Results on synovial hypertrophy in this study therefore represent both synovial hypertrophy with and synovial hypertrophy without haemosiderin deposits.…”
Section: Discussionmentioning
confidence: 95%
“…), and a musculoskeletal sonographer with greater than 20 years of experience (R.E.M.). Images obtained during the 600 musculoskeletal US joint evaluations (≈6000 views) were reviewed by the 3 members of the nominal group, with a special focus on results from an accompanying pathologic tissue validation study in hemophilic arthropathy, in which musculoskeletal US views were aligned with corresponding views of conventional and ultrashort time‐to‐echo magnetic resonance imaging, obtained simultaneously. This review defined the following: (1) the extent to which musculoskeletal US discriminated different types of pathologic tissue for descriptive charting of findings; (2) the feasibility of direct measurements of soft tissue expansion, osteochondral changes, and cartilage thickness; and (3) the standardized locations of US assessments.…”
Section: Methodsmentioning
confidence: 99%
“…OMERACT is a widely accepted international initiative, whereby the cornerstones of validation are composed of correct tissue annotation, the establishment of intra‐rater, inter‐rater, and inter‐operator reliability, and clinical applicability for specific disease states and patient cohorts, emulating the OMERACT filter components truth, discrimination, and feasibility . Along OMERACT recommendations, we recently established the extent of pathologic tissue discrimination with musculoskeletal US specific to hemophilic joints by comparison with conventional and ultrashort time‐to‐echo magnetic resonance imaging …”
mentioning
confidence: 99%
“…Electives include Coagulation Laboratory, Blood Banking/Transfusion Medicine, Vascular Medicine, and Neuroimaging. A growing number of HTCs are using point‐of‐care musculoskeletal ultrasound (MSKUS) such that trainees have the opportunity to learn this skill for the evaluation of joint health . Hay et al recently identified training in the aged population and global hematology as two keys components of advanced hematology training that have previously been neglected and are urgently needed .…”
Section: Training Programsmentioning
confidence: 99%